S100A4 protects the myocardium against ischemic stress - Doroudgar, Shirin; Konstandin, Mathias; Völkers, Mirko (Journal of molecular and cellular cardiology, 2016)
Myocardial infarction is followed by cardiac dysfunction, cellular death, and ventricular remodeling, including tissue fibrosis. S100A4 protein plays multiple roles in cellular survival, and tissue fibrosis, but the relative role of the S100A4 in the myocardium after myocardial infarction is unknown. This study aims to investigate the role of S100A4 in myocardial remodeling and cardiac function following infarct damage. S100A4 expression is low in the adult myocardium, but significantly increased following myocardial infarction. Deletion of S100A4 increased cardiac damage after myocardial infarction, whereas cardiac myocyte-specific overexpression of S100A4 protected the infarcted myocardium. Decreased cardiac function in S100A4 Knockout mice was accompanied with increased cardiac remodeling, fibrosis, and diminished capillary density in the remote myocardium. Loss of S100A4 caused increased apoptotic cell death both in vitro and in vivo in part mediated by decreased VEGF expression. Conversely, S100A4 overexpression protected cells against apoptosis in vitro and in vivo. Increased pro-survival AKT-signaling explained reduced apoptosis in S100A4 overexpressing cells. S100A4 expression protects cardiac myocytes against myocardial ischemia and is required for stabilization of cardiac function after MI.